2018
DOI: 10.5194/angeo-36-25-2018
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the dependence of seismo-ionospheric coupling on the magnetic field inclination

Abstract: Abstract. Infrasound generated during a seismic event upon reaching the ionospheric heights possesses the ability to perturb the ionosphere. Detailed modelling investigation considering 1-D dissipative linear dynamics, however, indicates that the magnitude of ionospheric perturbation strongly depends on the magnetic field inclination. Physics-based SAMI2 model codes have been utilized to simulate the ionosphere perturbations that are generated due to the action of the vertical wind perturbations associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…It is found one-to-one correspondence between Doppler signal and seismic waves (e.g., Yuen et al, 1969). Catherine et al (2017) also have investigated the Nepal earthquake using GPS TEC observations and suggested that these Rayleigh wave induced acoustic waves are not propagated to northern latitudes but they propagated to southern latitudes which is in agreement with Reddy and Gopi (2015) but in contrast to Joshi et al (2017) modeling work. This can be overcome by using rapid run ionograms (high resolution) to study the infrasonic wave signatures in the ionograms.…”
Section: Resultsmentioning
confidence: 56%
See 4 more Smart Citations
“…It is found one-to-one correspondence between Doppler signal and seismic waves (e.g., Yuen et al, 1969). Catherine et al (2017) also have investigated the Nepal earthquake using GPS TEC observations and suggested that these Rayleigh wave induced acoustic waves are not propagated to northern latitudes but they propagated to southern latitudes which is in agreement with Reddy and Gopi (2015) but in contrast to Joshi et al (2017) modeling work. This can be overcome by using rapid run ionograms (high resolution) to study the infrasonic wave signatures in the ionograms.…”
Section: Resultsmentioning
confidence: 56%
“…However, Doppler shift of the HF radar system can't provide altitude information as it is limited by its operating frequency. But Joshi et al (2017) has considered that rupture is uniform in the north and south direction. The high resolution ionosonde observations as presented above show wave perturbations possibly linked to acoustic and atmospheric gravity waves during the time of earthquake.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations